Faktor-Faktor Yang Berhubungan Dengan Pencegahan Penyakit Demam Berdarah Dangue (DBD) Di Desa Pulau Panggung Wilayah Kerja UPTD Puskesmas Tanjung Agung Kabupaten Muara Enim Tahun 2023 - Lastini Asmar; Yulis Marita; Eka Joni Yansyah (Pusat Riset dan Inovasi Nasional, 2023)
Background: World Health Organization (WHO) stated that the number of reported cases of dengue fever has increased more than 8-fold over the last 4 years, from 505,000 cases increasing to 4.2 million in 2022. The number of reported deaths has also increased from 403 to 960. Not only is the number of cases increasing as the disease spread to new regions including Asia, but explosive outbreaks also occurred. The threat of a possible dengue fever outbreak now exists in Asia.Objective: Know the factors related to preventive measures for dengue fever dengue (DBD) in Pulau Panggang Village, Tanjung Agung Community Health Center, Muara Enim Regency in 2023 Method: This research has an analytical approach cross sectional use chi square. This research sample uses probability sampling totaling 91 respondents. This research uses univariate and bivariate analysis. Results: The results of bivariate analysis showed a significant relationship between knowledge and prevention of dengue fever range p-value 0.003, there is a significant relationship between attitude and prevention of dengue fever range p-value 0.002, there is a significant relationship between education and the prevention of dengue fever range p-value 0.003, there is a significant relationship between knowledge and prevention of dengue fever range p-value 0,004. Conclusion: There is a significant relationship between knowledge, attitudes, education and family support and the prevention of dengue fever.